Evaluation of Prepubertal Patients with Suspected Neurosecretory Dysfunction of Growth Hormone Secretion: Diagnostic Steps and Treatment Response. (23rd February 2017) - Sydlik, Carmen; Weißenbacher, Claudia; Roeb, Julia; Bechtold-Dalla Pozza, Susanne; Schmidt, Heinrich
Abstract : Background and Aims. Existence and diagnostic procedures of neurosecretory dysfunction of growth hormone (NSD) are still a matter of debate. The aim of our study was (a) to find out if prediagnostic auxological and laboratory data could serve as an indicator for pathologic and normal spontaneous GH-secretion and (b) to evaluate the response to GH-therapy in NSD-patients. Methods. Of 90 children (unicentric study) with normal response to GH-stimulation tests, in whom 12-hour night profiles for GH-secretion were performed, 49 were diagnosed with NSD (NSD group). Their auxologic data, IGF-I/IGFBP3-levels as well as the night profiles, were analysed and compared to those of the non-NSD group. Additionally, follow-up auxological data of the GH-treated NSD-patients were collected. Results. Prediagnostic auxologic and laboratory data did not differ between the two groups. Instead, for all analysed criteria of spontaneous GH-secretion (number of peaks, maximal and mean secretion) a significant difference was found. Children with NSD showed a good response to GH-treatment after 1 (Δ H-SDS +0, 77 ± 0, 48) as well as 4 years (+1, 51 ± 0, 75). Conclusion. According to our results, analysing spontaneous GH-secretion remains the only method to identify NSD. Yet, as response to GH-treatment is comparable to results in idiopathic GHD, it is worth to consider this diagnosis.